Efektivitas Penerapan Metode Diskusi dengan Pendekatan Matematika Realistik (PMR) Ditinjau dari Tipe Kepribadian Siswa Kelas VIII SMP Negeri di Kabupaten Lampung Timur - Desty Septianawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2014)
The aims of this research are to know: (1) Which one more effective, learning using discussion with realistic mathematics  approach or a conventional learning. (2) Which one gives better mathematics learning achievement, student with personality types Sanguine or Phlegmatis. (3) Which one more effective for each personality typeof students, learning using discussion withPMR or a conventional learning.This research used quasi experimental method with its population included all of students of state junior high school in East Lampung Regency. Sampling was done by stratified cluster random sampling. The size of the samples was 202 students. The data collection technique were the document that was the last of examination theseven grade for initial capability data before the experiment, achievement tests for mathematics student achievement data, and questioner of personality types. The data was analyzed using analysis of variance. The conclusions of the research were as follows: (1) learning mathematics using discussion with PMR is more effective than learning mathematics usingdiscussion with conventional approach. (2) Students with personalitytypesof Sanguinenor Phlegmatis have the same mathematics achievement. (3) For each personality type of students, learning using discussion with PMR approach is more effective than learning mathematics the method of discussion withconventional approach.